HADIST SEBAGAI SUMBER KEARIFAN LOKAL ACEH DALAM QANUN DAN UNDANG-UNDANG OTONOMI KHUSUS - Sayuti, Sayuti; Wahid, Abdul (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The problem regarding hadith as a source of local Acehnese wisdom in the qanun and special autonomy laws lies in the challenge of integration between the teachings of Islam and the dynamics of modern law that prevail. Its application in the qanun and laws often encounters obstacles in balancing the interests of religion, local culture, and the development of broader national law. This research uses the library research method, which focuses on collecting secondary data through literature studies. The results of the research show that: 1). The reason for using hadith as a source of local Acehnese wisdom in the formation of qanun and special autonomy laws is because it has moral and ethical values that are relevant to the social life of the Acehnese people, the majority of whom are Muslims. In the context of special autonomy, hadith is used to strengthen Acehnese religious and cultural identity in the formation of qanun and laws and regulations that are in line with Islamic sharia principles. 2). The role of hadith as a source of local Acehnese wisdom in the formation of qanun and special autonomy laws is that hadith acts as a normative basis in formulating qanun and laws in Aceh, by providing guidelines in policy formulation that includes social, economic, and legal aspects. 3). The form of application of hadith as a source of local wisdom in Aceh in the formation of qanun and special autonomy laws is seen in the arrangement that includes Islamic criminal law, muamalah, and education, by adjusting Islamic norms and local wisdom of Aceh. Hadith is used as a guideline in formulating fair rules, prioritizing social justice, and maintaining the morality of society according to Islamic teachings.